2022
DOI: 10.1093/mnras/stac183
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of satellite galaxies of Milky Way analogues: reconciling theory and observations

Abstract: The vast majority of low-mass satellite galaxies around the Milky Way and M31 appear virtually devoid of cool gas and show no signs of recent or ongoing star formation. Cosmological simulations demonstrate that such quenching is expected and is due to the harsh environmental conditions that satellites face when joining the Local Group (LG). However, recent observations of Milky Way analogues in the SAGA survey present a very different picture, showing the majority of observed satellites to be actively forming … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 57 publications
9
55
0
Order By: Relevance
“…Using the ARTEMIS simulations, Font et al (2022) found a quiescent fraction similar to the LG and other simulations. They defined a galaxy as quiescent if its instantaneous specific star formation rate is zero at 𝑧 = 0, and they verified that this agrees with lookback time and time-averaged sSFR criteria.…”
Section: Comparison To Other Simulationssupporting
confidence: 74%
See 4 more Smart Citations
“…Using the ARTEMIS simulations, Font et al (2022) found a quiescent fraction similar to the LG and other simulations. They defined a galaxy as quiescent if its instantaneous specific star formation rate is zero at 𝑧 = 0, and they verified that this agrees with lookback time and time-averaged sSFR criteria.…”
Section: Comparison To Other Simulationssupporting
confidence: 74%
“…Our results on host mass effects generally agree with previous studies of simulations and observations that leverage larger samples of MW-mass hosts. Font et al (2022) found lower quiescent fractions of satellites (𝑀 * ≈ 10 6.5−9.5 M ) around less massive hosts in the ARTEMIS simulations (45 hosts with 8×10 11 < 𝑀 200m /M < 2 × 10 12 ). Carlsten et al (2022) also found a similar trend in observations where the overall quiescent fraction of satellites (𝑀 𝑉 < −9 mag, 𝑀 * 5 × 10 5 M ) increases with the luminosity of observed MW-like hosts (30 host galaxies with 𝑀 𝐾 𝑠 < −22.1 mag) in the Local Volume (𝐷 < 12 Mpc).…”
Section: Mw-mass Host Environmentmentioning
confidence: 72%
See 3 more Smart Citations

Once in a blue stream

Martínez-Delgado,
Roca-Fàbrega,
Gil de Paz
et al. 2024
A&A